Electricity Production from Food Waste Leachate (Fruit and Vegetable Waste) using Double Chamber Microbial Fuel Cell: Comparison between Non-aerated and Aerated Configuration - Prasidha, Willie (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Two double chamber microbial fuel cells with different configurations were developed to produce electricity food waste leachate and studied for 30 days. Anode and Cathode were made by uncoated carbon felt and graphite rods. Â Food waste and water were incubated into the reactor. After more than 30 days, leachate with the neutral condition (pH 6.9) was collected from the leachate reactor. 500 ml leachate was used in the anode chamber and 500 ml catholyte was used in the cathode chamber. The first configuration, non-aerated MFC, the maximum OCV, maximum power density, average power density, and maximum current density were 373 mV, 25.7 mW/m2, 3.7 mW/m2, and 21.4 mA/m2 respectively. For the second configuration, aerated MFC, maximum OCV, maximum power density, average power density, and current density were 404 mV, 25.7 mW/m2, 6.1 mW/m2, and 21.4 mA/m2 respectively. Aerated MFC had higher maximum OCV and average power density than non-aerated MFC. From the study, supplying continuous dissolved air (oxygen) in the cathode chamber can produce more voltage and average power density in double chamber microbial fuel cell.